Identifikasi Mikroorganisme yang Terlibat dalam Proses Fermentasi Tape Singkong (Manihot Utilissima) secara Mikroskopis dan Analisis - Ni’matullathifah; Ardi Mustakim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Cassava (Manihot utilissima) fermentation is a traditional process that has long been used to produce tape singkong, a distinctive Indonesian fermented food product. This fermentation process relies on natural or inoculated microorganisms, such as yeast, mold, and lactic acid bacteria, which play a crucial role in converting starch in cassava into simpler sugars. This process results in the unique taste of tape, characterized by a balance of sweet and sour flavors and a soft texture that distinguishes tape singkong. This study aims to identify the microorganisms involved in the fermentation process of tape singkong through microscopic observation. Tape samples were collected at various stages of fermentation to obtain a comprehensive picture of the microbial changes occurring during the fermentation process. Gram staining was used to differentiate microbes based on their cell wall characteristics, while the morphology of molds and yeasts was examined to identify the types of microorganisms involved in the fermentation. The study's findings revealed that the microorganisms involved in cassava fermentation included a variety of species, including Saccharomyces cerevisiae (yeast), Lactobacillus spp. (lactic acid bacteria), and filamentous molds such as Rhizopus spp. These microorganisms play vital roles in the fermentation process by breaking down starch into simpler sugars, which contribute to the characteristic sweet and sour taste and soft texture of tape. This microscopic identification underscores the significant role of microbial activity in the success of the cassava fermentation process and provides insights into the microbiological profile of traditional fermented foods. These findings also open up opportunities for further development in biotechnology and the food industry, exploring the potential of local microorganisms to produce higher-quality and more diverse fermented food products.